Dynamic balance standard values of combat soldiers readiness - Endang Ernandini; Fidelia Adeline Cahyadi; Muhammad Fauzi Faturohman Sonjaya; Dea Chandra Trinita; Wenseslaus Kostradilo Dasepta (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: The Medical Rehabilitation Unit provides post-injury rehabilitation for soldiers and staff at the Gatot Soebroto Army Central Hospital (RSPAD-GS), where the risk of injury is high. The goal of post-injury rehabilitation is to regain readiness for duty. Reference values are needed for preventive measures against injury and as evaluation criteria for post-injury lower limb recovery. The Star Excursion Balance Test (SEBT) was selected because it can be easily and independently performed by soldiers and all RSPAD-GS personnel. This study also sought reference values for other dynamic balance tests using the advanced iMoove device, which is already available at RSPAD-GS but lacks clear reference values. Methods: This study design is a cross-sectional comparison. It included 15 healthy/uninjured soldiers (NS) and 15 soldiers with lower limb injuries (IS). All soldiers were males aged 20 to early 30s and met the inclusion criteria. Both the NS and IS groups underwent the SEBT and iMoove tests. Results: The SEBT scores for the healthy IS limb were significantly lower than those for the NS limb (p < 0.05) in 5 of the 8 directions studied. The SEBT scores for the injured IS limb were significantly lower than those for the healthy IS limb in 5 of the 8 directions studied (p < 0.05). The NS SEBT values were: anterior 94.40%, anteromedial 98.13%, medial 97%, posteromedial 99%, posterior 94.67%, posterolateral 97.86%, lateral 86.53%, and anterolateral 86.40%. In the study using the iMoove device, a significant difference was found between IS and NS in iMoove phase III with a value of 8.2 (p=0.007). Conclusion: These reference values are valid for individuals aged 20–early 30s. Dynamic balance scores in the IS group were significantly lower than those in the NS group, even though assessments were conducted in both groups on the uninjured limb. NS dynamic balance scores can be used as reference values for preventive measures and recovery from lower limb injuries. Reference values for the iMoove device must be above 8.2 for each phase. Medical rehabilitation therapy takes a holistic approach to the patient, involving both the injured and uninjured sides to restore functional daily activities.